The Influence of Information Quality, Convenience, and Customization on Purchase Intention through Perceived Value: A Study of Customized Cake Purchases via Social Media - RA. Intan Permata Buana; Sabrina O. Sihombing (Universitas Pelita Harapan, 2025)
This study aims to examine the effects of information quality, convenience, and customization on purchase intention, with perceived value as a mediating variable, in the context of food and beverage SMEs using social media. The research focuses on Instagram users who have seen, interacted with, or purchased customized cakes. Data will be collected through a survey of 240 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. This study is expected to contribute theoretically by extending the Theory of Planned Behavior to the domain of digital consumer behavior and methodologically by demonstrating the application of Importance-Performance Map Analysis (IPMA) in PLS-SEM. Practically, the research is anticipated to provide insights for SMEs in enhancing perceived value through accurate information, seamless convenience, and personalized services to strengthen purchase intention in competitive online markets. In addition, the findings are expected to guide digital marketing strategies for SMEs in building sustainable customer relationships and long-term competitiveness.